Aṅgrezī-Pañjābī takanīkī shabadāwalī, aratha-wigiāna te ārathika aṅkaṛā-wigiāna (economics & economic statistics) (Pañjāba Saṭeṭa Yūnīwarasiṭī Ṭaikasaṭa-buka Boraḍa, 1970)
Dictionary of technical terms, economics.